THE EFFECT OF AN INNOVATIVE FERTILIZER OF DIGESTATE AND WOOD ASH MIXTURES ON WINTER GARLIC PRODUCTIVITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Garlic (Allium sativum L.) is a widespread crop in vegetable production. The popularity of garlic is due to its bactericidal and antioxidant properties. Digestate and wood ash are the by-products of cogeneration plants. The digestate is rich in nutrients, can provide a large part of the nutrients needed by the plant during the growing season, as well as improves the soil structure. Wood ash contains small amounts of phosphorus and potassium and is strongly alkaline (pH 8–12) due to the oxides in its composition, mostly calcium carbonate. The purpose of the study was to determine the effect of fertilizer rates of the digestate and wood ash mixtures on winter garlic productivity and harvest quality. Field trials with the winter garlic variety 'Lubaša' were established in sod clay, loamy soil. In the garlic plantation, different variants of fertilizer mixtures were used – they contained pig or cattle manure or plant residue digestate, and wood ash. The ratio of digestate and wood ash in the mixtures was 3:1; fertilizer rates for winter garlic were 15 and 30 t ha-1. In the study, the different types of fertilizers showed different effects on the yield and quality of winter garlic.